Enzymatic technology for Sea buckthorn oil extraction and its biochemical analysis - Munkhbayar, D; Ariuntungalag, J; Delgersuuri, G; Badamkhand, D (Mongolian Journal of Chemistry, 2014)
A research was conducted mix five Sea buckthorn berries harvested Mongolian Central Zone, and an integrated processing composed of an enzymatic unit operation and pulp oil and raw juice have been produced by centrifugal technology. For the extraction of Sea buckthorn oil, pectinase were used simultaneously hydrolyze Sea buckthorn berry pulp. In this study, the following commercial enzymes were evaluated in the enzymatic extraction of oil and raw juice from Sea buckthorn berry: Pectinase. Pectinase dose of 0.5 %, extraction time 120 minutes, hydrolysis temperature 55°C were found optimum, and maximum oilyieldof 5.0 - 5.1 % was achieved under these conditions, and the recovery of the optimized extraction process was calculated to 95.7 – 98.0 % based on 5.2 %theoreticaloil content of sea buckthorn fruit. In addition, physical and biochemical compositions of Sea buckthorn pulp oil was analyzed modern methods as HPLC, Spectrophotometer, Gravimeter, Pycnometer and Refractometers. Fatty acids by HPLC were identified in Pulp oil, mainly including 42,5% palmitoleic acid, 11.2 % linoleic acid, 1.2 % linolenic acid, 12.3% oleic acid, and unsaturated fatty acids occupied 70.9% of the total fatty acids. In conclusion, the enzymatic extraction process has thebenefitsof mild conditions, safe, fast for oil extraction, high yield, and pure juice after oil extraction. DOI: http://doi.dx.org/10.5564/mjc.v15i0.325 Mongolian Journal of Chemistry 15 (41), 2014, p62-65